1983
DOI: 10.1152/jappl.1983.54.2.371
|View full text |Cite
|
Sign up to set email alerts
|

Lung vessel leak precedes right ventricular hypertrophy in monocrotaline-treated rats

Abstract: Monocrotaline induces microvascular leak and pulmonary hypertension in rats. We have hypothesized that the leak is related in some way to the pulmonary hypertension and precedes it. In rats given 40 mg monocrotaline/kg body wt subcutaneously, lung wet weight-to-dry weight ratios and lung albumin content began to increase within the first 3 days and became maximal at 1 wk. Alveolar lavage fluid showed little or no increase in protein. Right ventricular hypertrophy increased progressively from 2 through 3 wk. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 0 publications
2
34
0
Order By: Relevance
“…vSMC phenotypic plasticity has been described in multiorgan development as well as in various adult diseases characterized by vascular remodeling (49,50). The plasticity of vSMCs is represented by 2 major phenotypes: differentiated and Vascular leak is a key indicator of vascular endothelial dysfunction and is known to precede remodeling, including both microvessel pruning and muscularization (68). Thus, our findings indicate that ABCG2 + MPC-to-pericyte differentiation is an important determinant in the maintenance of proper lung function and health.…”
Section: Discussionmentioning
confidence: 65%
“…vSMC phenotypic plasticity has been described in multiorgan development as well as in various adult diseases characterized by vascular remodeling (49,50). The plasticity of vSMCs is represented by 2 major phenotypes: differentiated and Vascular leak is a key indicator of vascular endothelial dysfunction and is known to precede remodeling, including both microvessel pruning and muscularization (68). Thus, our findings indicate that ABCG2 + MPC-to-pericyte differentiation is an important determinant in the maintenance of proper lung function and health.…”
Section: Discussionmentioning
confidence: 65%
“…Sugita etal. [2] stressed that cellular hyperplasia of the lung paralleled the extent of PH. Lafranconi and Huxtable [14] found that RNA synthesis and protein synthesis began to increase 1 week after MCT administration and last ed for a 3-week experimental period.…”
Section: Discussionmentioning
confidence: 99%
“…The thymidine incorporation rate began to increase somewhat at 3 days after MCT injection, and significantly increased thereafter, confirming earlier reports [12], whereas lungs from MCT + WEB-treated rats showed significantly lower activity when compared with MCT-treated rat lungs at 7 days after MCT injection. MCT causes a pulmonary vascular leak during the early injury phase [22]. Since treatment with PAF antagonist reduces the pulmonary vascular leak induced by MCT [15], and perhaps causes a reduction in the escape of plasma growth factors from the circulation [17], the reduction of the pulmonary vascular leak might be related to the reduction in lung DNA synthesis in the MCT + WEB rats.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of reduction in small arteries has not been precisely clarified, Schraufnagel and Schmid performed casts of the lung vessels in MCT-treated rats and suggested that the decrease in the density of vessels might be due to capillary and small vessel thrombosis [ 18]. It is well established that MCT-associated lung disease is associated with pulmonary vascular endothelial injury [15,22]. Since platelets aggregate at the site of endothelial injury [17], and since PAF may contribute to endothelial injury in MCT-induced lung disease [15], it is possible that the maintenance of regular arterial density in MCT-treated rat lungs by way of PAF antagonist treatment could be due to the prevention of in situ thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation